The FC & ZFC analysis and photocatalysis activity of RFeO3 orthoferrites (R = rare earth elements) - Nakhaei, Mehrnoush; Nobre, Marcos A.L. [UNESP]; Sabouri, Zahra; Darroudi, Majid; Khoshnoud, Davoud Sanavi; Khonakdar, Hossein Ali (Elsevier, 2025)
In this study, RFeO3 nanoparticles were synthesized by sol-gel method to investigate the magnetic and photocatalytic properties of these perovskites. The morphology of the samples were investigated by field emission scanning electron microscopy. Beside x-ray diffraction patterns showed the orthorhombic structure with Pbnm space group with no impurity. For magnetic study of the RFeO3 nanoparticles (NPs) the field-cooled and zero-field-cooled measurements were used. For this magnetic measurement, a quantum design PPMS system is used. In this way, the spin reorientation temperature (T SR ) and Neel temperature (T N ) of the samples were extracted, too. Next, diffuse reflectance spectroscopy analysis was used to calculate the band gap energy (E g ) of the samples according to the Kubelka-Munk function. The calculated values determined that the E g values became more by decreasing the ionic radius of the rare earth elements in RFeO3 NPs. At last, the photocatalytic activity of the RFeO3 NPs was studied by calculating the degradation of methylene Blue (MB) dye solution. Therefore, the results showed that LaFeO3 NPs has the highest degradation percent ~96 % in 120 min.